An Intelligent Agro-Cloud Framework For Efficient Crop Cultivation (Journal of Pharmaceutical Negative Results, 2023)
Agriculture is considered the backbone of the Indian economy. But, still, farmers are unable to get sufficient profit due to water scarcity, flooding, storm, insufficient labor, and poor agro marketing. Moreover, modern technologies are not practiced efficiently in farming due to ignorance, high cost, and small land size. The proposed cloud-based framework consists of three key layers i) input layer ii) storage and processing layer iii) application layer. The input layer collects data from various IoT devices like sensors, meters, cameras, robots (for weeding & spraying), drones, and satellite data. The agro-cloud stores and processes the input data from IoT devices at regular intervals of time. Layer 2 aids smart farming namely soil monitoring, crop growth, irrigation management, and pesticide& fertilizer control. Soft computing technologies such as artificial intelligence, neural networks, and machine learning algorithms can be employed to select the appropriate irrigation method based on the type of soil, crop, quality of water, and rainfall. The application layer interacts with the farmers through various applications like graphical user interface systems (GUI), SMS alerts, and IoT-based mobile applications. A farmer advisor mobile App is designed based on the recommended framework for efficient crop cultivation which provides timely information to farmers like formulating land, choosing seeds, planting, plant protection, and plant insurance. Thus, the proposed research aids the farmers in improving crop yield and reducing the workforce and resources.